Parametric Study on Dimensional Control of ZnO Nanowalls and Nanowires by Electrochemical Deposition - Pradhan Debabrata; Sindhwani Shrey; Leung KT (Nanoscale Research Letters, 2010)
Abstract A simple electrochemical deposition technique is used to synthesize both two-dimensional (nanowall) and one-dimensional (nanowire) ZnO nanostructures on indium-tin-oxide-coated glass substrates at 70°C. By fine-tuning the deposition conditions, particularly the initial Zn(NO3)2·6H2O electrolyte concentration, the mean ledge thickness of the nanowalls (50–100 nm) and the average diameter of the nanowires (50–120 nm) can be easily varied. The KCl supporting electrolyte used in the electrodeposition also has a pronounced effect on the formation of the nanowalls, due to the adsorption of Cl− ions on the preferred (0001) growth plane of ZnO and thereby redirecting growth on the (10 0) and (2 0) planes. Furthermore, evolution from the formation of ZnO nanowalls to formation of nanowires is observed as the KCl concentration is reduced in the electrolyte. The crystalline properties and growth directions of the as-synthesized ZnO nanostructures are studied in details by glancing-incidence X-ray diffraction and transmission electron microscopy.